2014
DOI: 10.3390/molecules190812789
|View full text |Cite
|
Sign up to set email alerts
|

Thiosulfoxide (Sulfane) Sulfur: New Chemistry and New Regulatory Roles in Biology

Abstract: The understanding of sulfur bonding is undergoing change. Old theories on hypervalency of sulfur and the nature of the chalcogen-chalcogen bond are now questioned. At the same time, there is a rapidly expanding literature on the effects of sulfur in regulating biological systems. The two fields are inter-related because the new understanding of the thiosulfoxide bond helps to explain the newfound roles of sulfur in biology. This review examines the nature of thiosulfoxide (sulfane, S0) sulfur, the history of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
118
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(125 citation statements)
references
References 125 publications
(177 reference statements)
2
118
0
Order By: Relevance
“…Yadav et al (63) also suggested that SSP4 is unlikely to detect low-molecular-weight persulfides in solution but instead detects thiosulfoxides [RS(ϭS)SR] and that SSP4 itself could bind to cysteine persulfides. The issue is further complicated by the possibility of tautomerization between thiosulfoxides and polysulfides (55). We have shown previously (8) and again in Fig.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Yadav et al (63) also suggested that SSP4 is unlikely to detect low-molecular-weight persulfides in solution but instead detects thiosulfoxides [RS(ϭS)SR] and that SSP4 itself could bind to cysteine persulfides. The issue is further complicated by the possibility of tautomerization between thiosulfoxides and polysulfides (55). We have shown previously (8) and again in Fig.…”
Section: Discussionmentioning
confidence: 89%
“…In order for H 2 S to persulfidate, either it, or the protein cystine sulfur, must first undergo a two-electron oxidation to sulfane sulfur (0 formal oxidation state), or both must undergo a one-electron oxidation, which is less likely. The sulfane (thiosulfoxide) sulfur in DADS (RSSR) and DATS (RSSSR), where R denotes the allyl groups, appears to be especially important in this regard, as it can tautomerize to RS(S)R and RS(S)SR, and this sulfur is highly reactive (55).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polysulfides were proposed to be the bioactive molecules responsible for "H 2 S signaling" and much of the physiological action of sulfide in cells (31,48,49). In addition, they are believed to act as storage or buffer molecules of H 2 S, with surprisingly high concentrations measured in murine organs/tissues (31).…”
Section: Nomentioning
confidence: 99%
“…HS n − (and their organic counterparts) are not resistant to reducing conditions and high concentrations of thiols, and contain a highly reactive sulfane sulfur (49,50). Polysulfides were proposed to be the bioactive molecules responsible for "H 2 S signaling" and much of the physiological action of sulfide in cells (31,48,49).…”
Section: Nomentioning
confidence: 99%